Slow growing Squamous cell carcinoma over the back masquerading a pigmented naevus clinically - A rare case report - Anil Sunkara; R. Venkatesh; V. Srinivasan (Wolters Kluwer Medknow Publications, 2015)
Introduction: Slow growing pigmented squamous cell carcinoma is a rare entity. We present a 55 year old female who presented with a pigmented naevus of long duration which was excised and proven a squamous cell carcinoma and followed up with no recurrence. Conclusion: We would like to consider our case report to be alarming as the presentation was masquerading a benign lesion, and if overlooked may turn fatal both for the surgeon and the patient.